Jolly phonics Interactive Video Indonesian Language Content Beginning Reading Material for Grade I Elementary School Students - I Made Adi Sastrawan; Maria Goreti Rini Kristiantari (Mimbar Pendidikan Indonesia, 2025)
Several students still experience difficulties in early reading activities. The lack of instructional media used by teachers in teaching early reading to first-grade students has hindered the development of students' reading skills. Therefore, this study was conducted to analyze the effectiveness of interactive Jolly Phonics videos in the Indonesian language subject, specifically in early reading material. The subjects of this study included an instructional design expert, a subject matter expert, an educational media expert, and 10 first-grade students. This research employed a Research and Development (R&D) model, specifically using the ADDIE model. The methods and instruments for data collection included observation, interviews, and questionnaires. The data analysis techniques used were qualitative descriptive analysis, quantitative descriptive analysis, and dependent sample t-test. The results of the study show that the use of interactive Jolly Phonics videos in Indonesian language instruction for early reading material can improve early reading skills in first-grade students. The implication of this research is that the media is expected to assist students in learning to read and support teachers in developing instructional media.